An automatic approach for calibrating dielectric bone properties by combining finite-element and optimization software tools. Issue 12 (9th September 2016) - Su, Yukun; Kluess, Daniel; Mittelmeier, Wolfram; van Rienen, Ursula; Bader, Rainer
Abstract: The dielectric properties of human bone are one of the most essential inputs required by electromagnetic stimulation for improved bone regeneration. Measuring the electric properties of bone is a difficult task because of the complexity of the bone structure. Therefore, an automatic approach is presented to calibrate the electric properties of bone. The numerical method consists of three steps: generating input from experimental data, performing the numerical simulation, and calibrating the bone dielectric properties. As an example, the dielectric properties at 20 Hz of a rabbit distal femur were calibrated. The calibration process was considered as an optimization process with the aim of finding the optimum dielectric bone properties that match most of the numerically calculated simulation and experimentally measured data sets. The optimization was carried out automatically by the optimization software tool iSIGHT in combination with the finite-element solver COMSOL Multiphysics. As a result, the optimum conductivity and relative permittivity of the rabbit distal femur at 20 Hz were found to be 0.09615 S/m and 19522 for cortical bone and 0.14913 S/m and 1561507 for cancellous bone, respectively. The proposed method is a potential tool for the identification of realistic dielectric properties of the entire bone volume. The presented approach combining iSIGHT with COMSOL is applicable to, amongst others, designing implantable electro-stimulative devices or the optimization of electrical stimulation parameters for improved bone regeneration.